Peningkatan Kualitas dan Layanan Pendidikan di Kabupaten Pasuruan - Suadi, Suadi (Center of Education Journal (CEJou), 2022)
One form of the local government's commitment to improving human resources is through education. To produce a good and quality education process, of course, efforts must be made to provide quality education services. This research actually aims to find out all the efforts made by the Pasuruan Regency government in improving the quality and services of education in Pasuruan. Using descriptive qualitative method, this research explains several things related to improving the quality and service of education. In short, the results of the research show that there are effortsmade by the Regional Government of Pasuruan Regency in improving the quality and services of education, both in terms of regulations and regional planning